If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12a + 6b + -7a + 8b = 0 Reorder the terms: 12a + -7a + 6b + 8b = 0 Combine like terms: 12a + -7a = 5a 5a + 6b + 8b = 0 Combine like terms: 6b + 8b = 14b 5a + 14b = 0 Solving 5a + 14b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-14b' to each side of the equation. 5a + 14b + -14b = 0 + -14b Combine like terms: 14b + -14b = 0 5a + 0 = 0 + -14b 5a = 0 + -14b Remove the zero: 5a = -14b Divide each side by '5'. a = -2.8b Simplifying a = -2.8b
| -n+6=-6-4n-3n | | 3x-10=56 | | 2=x+x^2 | | 1/9*-8-9 | | N+5+7=8n-8n+4 | | 4=9.5 | | a^3-b^6= | | 9ln(x)=-1 | | (9x+24)+(6x+6)= | | -3x-2y+12=0 | | (4x+17)+28=6x | | 5+n=8n+5-4n | | 1.4z-5=3.7 | | 9(k-10)=k | | (x+3)2=36 | | 7p-1=-15 | | 5.3x-8.1=23.7 | | 900x=400+100x | | F(x)=3x+9Findf(2c-4) | | -8n+7n=-n | | 14x/15=7/30 | | 288*.30=x | | 3v-1+2+16=5+5v+4 | | X*.30=86.50 | | 3x-20=2x+2 | | 2(2x+1)-x=11 | | 12=2/3x-4 | | 2(5-3x)=3(4x+1) | | 12+5b=-2b-5b | | -top-4=to | | F(1)=3x^2-7 | | 3x+6y+1=10 |